PENGARUH PEMILU PRESIDEN INDONESIA TAHUN 2019 TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY STUDI PADA SAHAM LQ45 - Ivani, Nurul Saadah (AL-QARDH, 2019)
AbstractThis research uses event study analysis methode. The research periode used was 10 trading days, 5 covering days before the event and 5 days after the Indonesian presidential election 2019. The research is tested by using one sample t-test and paired sample t test. One sample t-test result indicates that abnormal return is significant negative before and after the event. However, the result of Paired Sample t-test shows that there is no significant difference between average abnormal return (ARR) before and after political event of Indonesian presidential election 2019. The result of Paired Sample t-test also shows that there is no significant difference between average trading volume activity (TVA) before and after political event of Indonesian presidential election 2019.Key word: Event Study, Abnormal Return, Trading Volume Activity, presidensial election.